Chapter Walling the peripheries: porous condominiums at Brazil's urban margins - Richmond, Matthew (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This chapter discusses a widespread but underexplored phenomenon in Brazilian cities: the growing presence of walls and other security infrastructures in low-income, peripheral neighborhoods. This practice can often take the form of bounded and internally regulated regimes of residential organization at a hyper-local scale, associated with the emic term condomínio (condominium). The authors propose the concept of "walling" to theorize the practices of socio-material assembly through which peripheral condominiums emerge, driven by the efforts of urban subjects to reconstruct a sense of well-being within environments experienced as precarious and insecure. While walling can significantly reshape socio-spatial relationships and everyday flows of bodies, the authors argue that broader social conditions and relationships in peripheries tend to promote forms of spatial and temporal porosity that weaken or even undermine these regimes of self-segregation. The chapter explores varying dynamics of peripheral condominiums through the presentation of contrasting case studies from three different Brazilian cities: a recently completed Minha Casa Minha Vida (My House My Life) public housing project in Porto Alegre; a partially walled and symbolically partitioned favela in Rio de Janeiro; and an occupied and subsequently formalized public housing project in São Paulo.